Developing an In Vitro Model to Screen Drugs for Nerve Regeneration. Issue 10 (17th October 2018) - RAYNER, MELISSA L. D.; LARANJEIRA, SIMÃO; EVANS, RACHAEL E.; SHIPLEY, REBECCA J.; HEALY, JESS; PHILLIPS, JAMES B.
ABSTRACT: Peripheral nerve injuries (PNI) have a high prevalence and can be debilitating, resulting in life‐long loss or disturbance in end‐organ function, which compromises quality of life for patients. Current therapies use microsurgical approaches but there is the potential for enhancing recovery through other therapeutic modalities such as; cell‐based conduits, gene therapy and small molecules. A number of molecular targets and drugs which have the potential to improve nerve regeneration have been identified, however, there are challenges associated with moving therapies toward clinical translation. Due to the lack of detailed knowledge about the pro‐regenerative effect of potential drug treatments, there is a need for effective in vitro models to screen compounds to inform future pre‐clinical and clinical studies. The interaction between regenerating neurites and supporting Schwann cells is a key feature of the nerve environment, therefore, in vitro models that mimic this cellular association are useful tools. In this study, we have investigated various cell culture models, including simple monolayer systems and more complex 3D‐engineered co‐cultures, as models for use in PNI drug development. Anat Rec, 301:1628–1637, 2018. © 2018 The Authors. The Anatomical Record published by Wiley Periodicals, Inc. on behalf of American Association of Anatomists.